Full-field phase error compensation method based on relationship between unwrapped phase and phase error. Issue 16 (20th September 2018) - Chen, Cheng; Cao, Yiping; Wan, Yingying; Fu, Guangkai; Wang, Yapin; Li, Chengmeng
ABSTRACT: The three-dimensional reconstruction in phase-measuring profilometry (PMP) usually involves the phase error caused by the gamma effect of the projector. In this study, the relationship between the unwrapped phase and the phase error of every pixel is analysed, and an effective full-field phase error compensation method based on this relationship is proposed for the reduction of every pixel error. In our optimized PMP system, the full-field phase error can be detected by directly fitting the unwrapped phase of the reference plane. In addition, the relationship between the unwrapped phase and the phase error can be established by creating a phase-error lookup table for the phase error compensation of every pixel. The experimental results demonstrate the effectiveness of the proposed method in practical PMP, and the measurement errors can be reduced by a factor of least 10.